High Prevalence of Antibiotic Resistance in Iranian Helicobacter pylori Isolates: Importance of Functional and Mutational Analysis of Resistance Genes and Virulence Genotyping - Smith, Sinead (My University, 2019)
The high prevalence of antibiotic resistance in Helicobacter pylori has become a great challenge in Iran. The genetic mutations that contribute to the resistance have yet to be precisely identified. This study aimed to investigate the prevalence of antibiotic resistance and virulence markers in Iranian H. pylori isolates and to analyze if there is any association between resistance and genotype. Antibiotic susceptibility patterns of 68 H. pylori isolates were investigated against metronidazole, clarithromycin, amoxicillin, rifampicin, ciprofloxacin, levofloxacin, and tetracycline by the agar dilution method. The frxA, rdxA, gyrA, gyrB, and 23S rRNA genes of the isolates were sequenced. The virulence genotypes were also determined using PCR. Metronidazole resistance was present in 82.4% of the isolates, followed by clarithromycin (33.8%), ciprofloxacin (33.8%), rifampicin (32.4%), amoxicillin (30.9%), levofloxacin (27.9%), and tetracycline (4.4%). Overall, 75% of the isolates were resistant to at least two antibiotics tested and considered as a multidrug resistance (MDR) phenotype. Most of the metronidazole-resistant isolates carried frameshift mutations in both frxA and rdxA genes, and premature termination occurred in positions Q5Stop and Q50Stop, respectively. Amino acid substitutions M191I, G208E, and V199A were predominantly found in gyrA gene of fluoroquinolone-resistant isolates. A2143G and C2195T mutations of 23S rRNA were found in four clarithromycin-resistant isolates. Interestingly, significant associations were found between resistance to metronidazole (MNZ) and cagA-, sabA-, and dupA-positive genotypes, with p = 0.0002, p = 0.0001, and p = 0.0001, respectively. Furthermore, a significant association was found between oipA “on” status and resistance to amoxicillin (AMX) (p = 0.02). The prevalence of H. pylori antibiotic resistance is high in our region, particularly that of metronidazole, clarithromycin, ciprofloxacin, and MDR. Simultaneous screening of virulence and resistance genotypes can help clinicians to choose the appropriate therapeutic regime against H. pylori infection.
PUBLISHED
PMID: 31744181
Keywords: Helicobacter pylori; Resistance genes; Mutations; Virulence genotype; cagPAI intactness; Genes & Society; Immunology, Inflammation & Infection